Anxiety Management of Patients First Time to The Dentist for Dental Extraction - Bambang Tri Hartomo; Saraya Hasyyati Adani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: Dental anxiety is a problem that often occurs in patients who will undergo dental treatment. Dental anxiety is a complex, multidimensional phenomenon, and there is no single variable that is the main cause. Dental anxiety is known to be a risk factor that causes various conditions such as pain perception, so that patients refuse to do dental work, especially invasive dental treatments such as tooth extraction. Purpose: The aim of this literature study is to provide information and knowledge about the management and treatment of dental anxiety in patients who come to the dentist for the first time for tooth extraction. Literature Study: This literature study was conducted using indexed and accredited national and international journals and provides information about the techniques that make the patient comfortable and reduce patient anxiety, as well as equipment that can be used in the extraction process that is comfortable for the patient. Discussion: Before performing tooth extraction operator needs an in-depth history to find out the patient's medical history and lifestyle. The approach technique used is influenced by the patient's attitude. At the second visit, the patient appeared to be more ready to accept the extraction procedure after providing information and descriptions to be carried out by the operator. Conclusion: Operators need to understand techniques to reduce anxiety levels in patients, especially patients who have never visited a dentist. After tooth extraction is complete, the operator must also pay attention to the consequences arising from the procedure, and pay attention to the post-extraction instructions.